One-year intravenous immunoglobulin replacement therapy: efficacy in reducing hospital admissions in pediatric patients with Inborn Errors of Immunity - Karina Mescouto de Melo; Lucas Macedo Alves; Cláudia França Cavalcante Valente; Fabíola Scancetti Tavares (Elsevier, 2022)
Objectives: To compare the frequency of hospitalization in children with Inborn Errors of Immunity with antibody deficiency previous to intravenous immunoglobulin (pre- IVIG) with a one-year period after initial IVIG (post-IVIG). Methods: Medical reports of 45 patients during an eight-year period were reviewed from 2018 to 2019. Wilcoxon-test was used for related samples. Results: Forty-five children were included in the study, aged 29-249 months of age, and most of them (64.4%) were males. Median ages at onset symptoms and at diagnosis were 6 and 73 months old, respectively. Specific antibody deficiency and unclassified hypogammaglobulinemia were the predominant diagnoses (31.1% and 17.8%, respectively). X-linked agammaglobulinemia, Hyper IgE syndrome, Hyper IgM, transient hypogammaglobulinemia of infancy, and Common Variable Immunodeficiency (CVID) were also reported, in a low frequency. Forty-four (97.8%) patients were hospitalized before IVIG, and 10 patients (22.2%) after. Annual mean hospital admission reduced from 2.5 to 0.5, pre and post-IVIG, respectively (p < 0.0001). Mean length of stay (LOS) reduced from 71 to 4.7 days/year (p < 0.0001) in general ward and in the PICU from 17.2 days/year to zero (p < 0.0002). Pneumonia was the main cause of hospital admission with a reduction in the number of episodes per patient from an average of 2.2-0.1 per year (p < 0.001). Concomitant use of antibiotic prophylaxis did not influence the number of hospital admission. Conclusion: One-year intravenous IVIG significantly decreased the number of hospitalizations and length of stay in children with impaired antibody production. Social and economic impacts would be required.